Variations in Hematologic Responses to Increased Lead Absorption in Young Children - Chisolm, J. Julian; Mellits, E. David; Keil, Julian E.; Barrett, Maureen B. (Environmental health perspectives, 1974)
In the study of human populations, much emphasis is placed on the concentration of lead in whole peripheral blood. There is a considerable body of evidence which indicates that this measurement reflects recent and current assimilation of lead. While broad ranges in blood lead concentration have been associated with differing risks of toxicity for groups, it is not a precise index of adverse effect per se, even at elevated levels. Within the red blood cell itself there is not a close association between the concentration of lead and such adverse metabolic effects as the increased loss of potassium caused by lead. Above the apparent "threshold zone" of approximately 30-50 μg Pb/100 ml whole blood, equivalent metabolic effects on heme synthesis may be seen over an interval of at least 20 μg Pb/100 ml whole blood. This variation will be examined with particular reference to the interrelationship between the concentrations of lead and protoporphyrin in peripheral blood. The data indicate that limitations in both precision and accuracy of measurement account for a relatively small fraction of the observed variations. Together with other experimental and clinical information, they suggest that concurrent dietary deficiency of iron may be one of the important modifying factors in the responses of subjects with increased lead absorption. It is suggested that suspected adverse effects upon the various organ systems associated with increased lead absorption be measured directly and that the CaEDTA mobilization test for lead should be more fully explored as a measure of the "metabolically active" fraction of the total body lead burden.